CAUSAL RELATIONSHIP BETWEEN MACROECONOMIC VARIABLES AND STOCK MARKET PRICES IN US - Madu, Chika Ozioma (My University, 2011)
The purpose of the study is to examine the causal relationship between the macroeconomic variables and stock market prices in the US. The empirical test was carried out using the Vector autogressive model and Granger causality test to analyze the causal relationship using data from 1985 to 2010. Firstly, the study used Augmented Dickey Fuller test to test the stationarity of the series and found that all the series are (stable) integrated of order zero I(0). The results of the empirical findings suggest the existence of causal relationship between the stock market and gross domestic product which represent the real activity in the US economy using the whole sample period from 1985 to 2010. This means that stock market prices can be used to predict gross domestic product in the US. However, relationship between the stock market returns and real activity appears to have broken down when regressions was run within the sub-sample periods of 1985 to 1995 and 1996 to 2010 respectively as there is no evidence of causality flows from S.P 500 index to gross domestic product. The result is consistent with the findings of Fama (1990) and Binswanger (2000) that studied similar research on this study. The possible reason for my results could be the existence of bull and bear in the stock market which influences the volatility of stock prices, globalization of financial markets and monetary policy shocks.
Keywords: Stock market returns; Macroeconomic variables; VAR; Granger causality test.; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|